Decent capitalism. A blueprint for reforming our economies - Dullien, Sebastian; Herr, Hansjörg; Kellermann, Christian (London, 2011)
"The recent crisis, created by finance capitalism, has brought us to the economic abyss. The excessive freedom of international markets has rapidly transformed into international panic, with states struggling to rescue and bail out a globalised financial sector. Reform is promised by our leaders, but in governments dominated by financial interests there is little hope of meaningful change.